« Naturalité » : concepts et méthodes appliqués à la conservation de la nature - Adrien Guetté (Unité Mixte de Recherche 8504 Géographie-cités, 2018)
In the current context of an increasing human encroachment on landscapes, the identification and cartography of the last remaining wild areas are increasingly challenging in the field of nature conservation. The concept of naturalité, a French-word derived from wilderness, is increasingly used in the literature to designate different qualities of an area, which can be antagonistic. However, there is still a lack of definition of this concept and they were few attempts to use it for mapping. Based on the French and international literature related to the definitions, concepts and methods to map and quantify the naturalité, we try to distinguish three different facets of this concept: the biophysical integrity, the spontaneity and the spatio-temporal continuities. When considering the example of the Marais poitevin, we propose a methodological approach to produce maps of these three facets, using specific indicators. Finally, we discuss the importance of using the concept of naturalité in nature conservation.